Farmers' Opinions about Bird Conservation and Pest Management on Organic and Conventional North Florida Farms - Susan K. Jacobson; Kathryn E. Sieving; Greg Jones; John McElroy; Mark E. Hostetler; Sarah W. Miller (EDIS)
This document is Circular 1426, one of a series of the Wildlife Ecology and Conservation Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: December 2002.